Analisis Reward System Terhadap Pengelolaan Manajemen Sumber Daya Manusia Dalam Upaya Meningkatkan Kinerja - Chalidatuzia Aurelika; Dian Marlina Verawati (CV ODIS, 2022)
The most important factor in an organization or a company is Human Resources. If you do not have good human resources then an organization will not run. This will also not work in harmony if there is no good management of human resources in an organization or company. A company or organization is formed and created based on a vision and mission to achieve goals for the benefit of humans and is managed by humans as well. So the importance of human resource management in the company environment. The purpose of this article is to explain a brief analysis of what managerial efforts can improve performance through a reward system to achieve organizational and company success. The method used in writing this article is to use a literature study by looking for references from several sources related to the research